Family’s Support in Activities Daily Living of Elderly in Pidie District - Risna Risna; Neila Fauzia (Science Midwifery, 2020)
The purpose of this study is to explore the family’s support in activities daily living of elderly in Pidie District. A descriptive phenomenological method was used and in depth-interview which was carried out face to face was done in collecting the data of this qualitative research. There were six research samples which were chosen by employing random sampling technique. Thematic analysis was conducted in analyzing the data and deciding the themes and categories of the data. Research data collection was conducted from 16 to 31 March 2020, during the COVID-19 pandemic period with due regard to health protocols. Based on the research that has been done, it can be concluded that the elderly with the treatment of families respect, love, attention to the elderly, the elderly feel happy, all informants say there is support from the family for the move because without the support of the elderly family will be lazy in the move, all the informants are disturbed activities caused by old age and often sick, and daily activities that need help, namely bathing, washing clothes and cooking. The results of this study are expected for families to be more active in encouraging the elderly to carry out daily activities and the family can help the activities daily living of the elderly that cannot be done independently.